Different NMDA receptor subtypes mediate induction of long‐term potentiation and two forms of short‐term potentiation at CA1 synapses in rat hippocampus in vitro. (9th January 2013) - Volianskis, Arturas; Bannister, Neil; Collett, Valerie J.; Irvine, Mark W.; Monaghan, Daniel T.; Fitzjohn, Stephen M.; Jensen, Morten S.; Jane, David E.; Collingridge, Graham L.
Key points: N ‐Methyl‐d ‐aspartate receptor (NMDAR)‐dependent potentiation of synaptic transmission is widely accepted as a cellular model of learning and memory. It is most often studied in the CA1 area of rat hippocampal slices where it comprises a decremental and a sustained phase, which are commonly referred to as short‐term potentiation (STP) and long‐term potentiation (LTP), respectively. In this study we show for the first time that STP and LTP are triggered by the activation of different classes of NMDARs and that STP itself comprises two pharmacologically and kinetically distinct components. We suggest that the mechanistic separation of STP and LTP is likely to have important functional implications in that these two forms of synaptic plasticity can subserve unique physiological functions in a behaving animal. Abstract Potentiation at synapses between CA3 and the CA1 pyramidal neurons comprises both transient and sustained phases, commonly referred to as short‐term potentiation (STP or transient LTP) and long‐term potentiation (LTP), respectively. Here, we utilized four subtype‐selective N ‐methyl‐d ‐aspartate receptor (NMDAR) antagonists to investigate whether the induction of STP and LTP is dependent on the activation of different NMDAR subtypes. We find that the induction of LTP involves the activation of NMDARs containing both the GluN2A and the GluN2B subunits. Surprisingly, however, we find that STP can be separated into two components, the major form of which involves activation of NMDARs containing both GluN2B and GluN2D subunits. These data demonstrate that synaptic potentiation at CA1 synapses is more complex than is commonly thought, an observation that has major implications for understanding the role of NMDARs in cognition.